Enhancing Leadership Skills: 2024 Training for Muhammadiyah Special Branch (PCIM) in the European and Mediterranean Area - Yordan Gunawan; Faiza Husnayeni Nahar; Sigit Arie Wibowo; Muhammad Annas; Izhan Fakhruzi (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
The 2024 Leadership Training and Upgrading event for PCIM Leaders and Members in the European and Mediterranean Regions, held in Madrid, Spain, on May 11-12, 2024, marked a significant milestone in Muhammadiyah’s history. Organized by PCIM Spain, this event brought together leaders and members from various countries for the first time, showcasing unprecedented cooperation and unity. The event, themed